The match each pair of rational numbers with their sum is:
[tex]\frac{2*(a-b)}{a^2b^2} = \frac{-2}{a^2b}+\frac{2}{ab^2}[/tex]
[tex]\frac{a-b^2}{a^2b^3} }=\frac{1}{ab^3} +\frac{-1}{a^2b}[/tex]
[tex]\frac{2ab-1}{4a^2b^2} }=\frac{1}{2ab} +\frac{-1}{4a^2b^2}[/tex]
[tex]\frac{2*(1-ab^2)}{a^2b^3} =\frac{2}{a^2b^3}+\frac{-2}{ab}[/tex]
Factoring
In math, factoring or factorization is used to write an algebraic expression in factors. There are some rules for factorization. One of them is a factor out a common term for example: x²-x= x(x-1), where x is a common term.
When you factor an expression using the rule a factor out a common term, it is possible simplify an expression
Then, you should factor and simplify each given algebraic expression.
- [tex]\frac{2*(a-b)}{a^2b^2} =\frac{2a-2b}{a^2b^2}=\frac{2a}{a^2b^2} -\frac{2b}{a^2b^2} =\frac{2}{ab^2} +\frac{-2}{a^2b}[/tex]
- [tex]\frac{a-b^2}{a^2b^3} }=\frac{a}{a^2b^3} -\frac{b^2}{a^2b^3} =\frac{1}{ab^3} +\frac{-1}{a^2b}[/tex]
- [tex]\frac{2ab-1}{4a^2b^2} }=\frac{2ab}{4a^2b^2} -\frac{1}{4a^2b^2} =\frac{1}{2ab} +\frac{-1}{4a^2b^2}[/tex]
- [tex]\frac{2*(1-ab^2)}{a^2b^3} =\frac{2-2ab^2}{a^2b^3}=\frac{2-2ab^2}{a^2b^3}=\frac{2}{a^2b^3}+\frac{-2}{ab}[/tex]
Learn more about the factoring here:
brainly.com/question/11579257
#SPJ1